Web-Based Financial Management Socialization And Training In Mushalla Al – Hikmah Rumai – Pekanbaru - Walhidayat; Pane, Eddissyah Putra; Toresa, Dafwen; Ayoe Jumala, Tjik; Permata Bunda, Yola (Mejuajua: Jurnal Pengabdian pada Masyarakat, 2023)
Financial management and governance training in mosques has a crucial role in ensuring efficient and transparent financial management. However, mosques often face challenges in managing finances properly due to limited knowledge and access to the latest technology. Therefore, this training aims to provide mosque administrators with a better understanding of modern financial management and to introduce web-based applications as an effective tool for mosque financial management. One of the unique features of this training is the introduction and training on using a web-based application that has been specifically designed for the needs of mosque financial management. This application includes various features, such as digital donation recording, expense tracking, automatic financial reports, and member and donor data management. By implementing this web-based application, it is hoped that mosque administrators can optimize their financial management, increase transparency, and minimize the risk of errors in managing mosque funds. This training was held collaboratively by a team of financial management experts, web application developers, and financial practitioners within the mosque. The results of this training are expected to help mosques achieve their financial goals in a sustainable manner, increase efficiency, and build community trust in the donations made.